Visualizing the invisible: the representation of reproductive labor in the ‘Other forms of work’ report from PNAD Contínua - Marques Santos, Leticia; Araujo Ferraz Oliveira, Gabriela; Marinho, Flávia (InfoDesign, 2025)
This article aims to analyze the data visualizations from the report “Other forms of work”, developed by the PNAD Contínua, emphasizing how reproductive labor (Federici, 2019) is measured and represented in its findings. To this end, a framework was developed based on three axes: (1) Context and Representation; (2) Information Structure; and (3) Data Production. The analysis revealed that the visualizations presented do not convey a critical and argumentative narrative about the phenomenon. Therefore, a non-oppressive, inclusive, and feminist approach is essential in the creation, collection, organization, and dissemination of socially oriented data.